2021
DOI: 10.1021/acs.jpclett.1c01021
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Improvement of Near-Infrared Photothermal Conversion Efficiency to 87.2% by Ultrafast Non-radiative Decay of Excited States of Self-Assembly Cocrystal

Abstract: Near-infrared (NIR) photothermal conversion is of great interest in many fields. Here, a self-assembly organic cocrystal (N,N,N′,N′-tetramethyl-p-phenylenediamine (TMPD) and pyromellitic dianhydride (PMDA)) with strong absorption in NIR range is constructed, with widespread absorption (200–1500 nm) and very high NIR photothermal conversion efficiency (87.2%). Essentially, in this cocrystal, a small HOMO–LUMO gap of donor–acceptor pair boosts the absorption ability of this cocrystal in the NIR range. The mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…9,20,21 The low gap offers the possibility to use EDA complexes as infra-red absorber for photovoltaics, photo-detectors and photo-thermal converters. [22][23][24] EDA complex formation was found also in photovoltaic systems, 25 where interaction between donor and acceptor is present only at the grain boundaries of separated D and A phases. The weakly absorbing EDA complex of zinc-phthalocyanine and fullerene C60 was used in infra-red detectors with optical cavities to increase the absorption of the complex.…”
Section: Introductionmentioning
confidence: 95%
“…9,20,21 The low gap offers the possibility to use EDA complexes as infra-red absorber for photovoltaics, photo-detectors and photo-thermal converters. [22][23][24] EDA complex formation was found also in photovoltaic systems, 25 where interaction between donor and acceptor is present only at the grain boundaries of separated D and A phases. The weakly absorbing EDA complex of zinc-phthalocyanine and fullerene C60 was used in infra-red detectors with optical cavities to increase the absorption of the complex.…”
Section: Introductionmentioning
confidence: 95%
“…[13][14][15] Narrow bandgap organic compounds possess strong absorption and/or emission in near-infrared (NIR) region and are required for solar-energy-related applications, bio-imaging and medical applications. [16][17][18][19][20] Generally, organic molecules with narrow bandgaps can be designed by introducing of electron donating-accepting (D-A) structures and quinoid structures. 21,22 N-Type organic semiconductors are essential materials in OFETs and OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…20 Li et al discovered a selfassembled organic cocrystal of N,N,N′,N′-tetramethyl-pphenylenediamine (TMPD) and pyromellitic dianhydride (PMDA), with high near-infrared photothermal conversion efficiency. 21 As small π-conjugated systems, single benzene luminescent molecules have attracted considerable research attention in the past few years due to their excellent properties and easy preparation. For instance, Zhang et al found two polymorphs of 2,5-bisIJ(thiophen-2-ylmethyl)amino)dimethyl terephthalate crystals exhibiting a flexible optical waveguide.…”
Section: Introductionmentioning
confidence: 99%